Competing challenges for immigrant seniors: Social isolation and the pandemic. Issue 5 (September 2021) - Johnson, Shanthi; Bacsu, Juanita; McIntosh, Tom; Jeffery, Bonnie; Novik, Nuelle
The pandemic has exposed and amplified complex and complicated health and societal challenges while offering immense opportunities to transform societies to improve health for all. Social isolation is a challenging and persistent issue experienced by many older adults, especially among immigrant and refugee seniors. Unique risk factors such as racism, discrimination, language barriers, weak social networks, and separation from friends and family predispose immigrant and refugee seniors to a higher risk of social isolation. The pandemic has magnified the unique risks and has highlighted the differential health and economic impacts. This article examines social isolation among immigrant and refugee seniors in Canada by focusing on the policy context, available programs and services to reduce social isolation, and the conceptualization and measurement considerations for advancing research to address social isolation among this growing population. Drawing on specific examples, we discuss immigration, aging, and social isolation within the context of Canada. While our article focuses on Canada as a case study, our discussion has relevancy and implications for other high-income countries with aging immigrant and refugee populations. In moving forward, we argue that a more complete and targeted understanding of social isolation is essential to informing program and policy development to support immigrant and refugee seniors in Canada and beyond. The transformation needed in our societies to create health for all requires strong equity and determinants of health perspective and a systems approach beyond health to ensure lasting change.